Optimization of γ-Aminobutyric Acid (GABA) Accumulation in Germinating Adzuki Beans (Vigna angularis) by Vacuum Treatment and Monosodium Glutamate, and the Molecular Mechanisms - Jiang, Xiujie; Xu, Qingpeng; Zhang, Aiwu; Liu, Yong; Zhao, Liqin; Gu, Liwei; Yuan, Jianbin; Jia, Hongdou; Shen, Xinting; Li, Zhijiang; Cao, Dongmei; Zhang, Dongjie (Frontiers in Nutrition, 2021)
To optimize the vacuum combined with MSG stress germination process condition,which accumulated GABA in germination adzuki beans, and revealed the molecular mechanism of GABA accumulation.The use of single-factor and response surface method, researched the effect of germination time, germination temperature, vacuum time and MSG concentration on GABA content,further explored the activity and gene expression of GAD, PAO critical rate restriction enzyme in GABA synthesis pathway. The results showed that the temperature of the immersion beige was controlled at 35℃, soaking time 16 h, the pH 5 were best. Germination optimal process were germination time 48 h, MSG concentration1.99mg/mL, germination temperature 31.49℃, vacuum time 15.83 h.Under this condition, the predicted value of GABA content was 443.57±7.18 mg/100g, compared to the GABA content of adzuki beans grains has increased 15.83 times.The vacuum +MSG (FZM) treatment has a maximum contribution rate of GABA to 38.29%, which can significantly increase GABA content, and this increase is due to GAD and PAO activity increasing. Different stress treatments have induced expression of VAGAD1, VAGAD2, VAGAD4, VAGAD6 gene, and FZM treatment can be adjacent to PAO, but found that the expression of PAO in 4 days of germination is significantly higher than the bud two days(P<0.05), but the overall PAO relational gene expression is lower than GAD relational genes, indicating that GABA in the pre-bud adzuki beans before relying on GABA branch, and the later polyamine degradation pathway has an important contribution to GABA enrichment.